Pengembangan Media Pembelajaran Kartu Belajar Augmented Reality (AR) Berbasis Assambler Edu pada Materi Sistem Ekskresi - Wanda Hamida; Muhammad Wajdi; Nurul Fadhilah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is Research and Development. The purpose of this study is to determine the validity and practicality of the Augmented Reality (AR) learning card media based on Assambler Edu for the excretory system. The population in this study were students of SMA Negeri 8 Makassar, with the selected sample being class XI Merdeka 5 of SMA Negeri 8 Makassar. The data collection technique used a validity and practicality assessment questionnaire. The collected data were data regarding the validity and practicality of the developed learning media. The results of the validity analysis show that the Augmented Reality (AR) learning card media based on Assambler Edu for the excretory system material obtained a score of 0.9, which is in the very valid category. Meanwhile, the practicality analysis results from the teacher obtained a score of 80.25%, and the student questionnaire analysis results obtained a score of 85.89%, which is in the range of 80% < P < 100%, with a very practical category. Therefore, it can be concluded that the Augmented Reality (AR) learning media based on Assembler Edu for the excretory system material is valid and practical.